TINGKAT RISIKO KARIES GIGI PERMANEN ANAK-ANAK TAMAN KANAKKANAK DI KOTA PALEMBANG DI MASA DATANG - Nur Adiba Hanum; Abu Hamid; Ismalayani`` Ismalayani (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Palembang, 2019)
Caries in children gets less attention from parents because of the assumption that the child's teeth will bereplaced by permanent teeth. The consequences of caries that occur from the beginning are a disorder ofmasticatory function, children are lazy to eat, and malnutrition can occur which affects the intelligence andactivity of children. The purpose of this study was to determine the potential risk level of permanent dentalcaries in children who are currently attending kindergarten in the city of Palembang and its relationship withcaries risk factors. This study is an epidemiological survey with a cross sectional approach. The population ofthis study was kindergarten children in Palembang city with a total sample of 767 children with a multi stagesampling technique. The results of this study indicate that the average risk level of permanent dental caries inchildren currently sitting in kindergarten is 81.9%, which is categorized as high caries risk. There was asignificant relationship between the risk level of permanent dental caries of kindergarten children in thePalembang city area with child behavior, maternal knowledge, acid pH of dental plaque, white spot on thesurface of milk teeth, and caries experience in milk teeth.